Energy Scenarios of Household Sector In Panauti Municipality For Sustainable Development and Energy Security - Dhaubanjar, Pramila; Nakarmi, Amrit Man; Bajracharya, Sushil B. (Journal of Advanced College of Engineering and Management, 2019)
This study aims to analyse energy scenarios of residential sector in Panauti Municipality for sustainable energy development and energy security. This study was done by conducting a questionnaire survey, and was supported by secondary data from various sources. Data analysis was carried out with the help of excel and LEAP software. From the results, total energy consumption of Panauti Municipality is 147 TJ in year 2016 with per capita is 4.72GJ and per capita emission 82kg. The main fuel for consumption in residential sector is firewood with share 44% then followed by LPG with 26% of total energy. Cooking is the most energy intensive end-use, accounting 60% of total energy consumption, followed by animal feed preparation 28%. It was seen that total electrification in all end-use can reduce energy demand by 57% and 35% respectively in AEL and SUD scenario and saved fuel import cost about NRs.235 million. in year 2050. Using nationally available electricity ensures energy security and has co-benefit of emission reduction.